The emerging leader stepping up in leadership - Shaw, Peter (London Canterbury press, 2013)
This practical and inspirational guide is for all who feel excited yet daunted at the prospect of taking on a leadership role, whether it be first-time leaders, or those taking on bigger, more demanding roles. This user-friendly companion will build confidence and increase competence. It focuses on identifying and strengthening core skills and gifts, including: building your supporter base living with your wobbles enjoying stepping into the unknown being willing to take responsibility motivating others making decisions well sitting lightly to uncertainty knowing how to handle conflict. Ideal if you are starting out on a new career or climbing the ladder, The Emerging Leader combines down-to-earth practical advice with timeless insights and wisdom.
Includes bibliographical references
Keywords: Leadership